Implementasi Media Wordwall pada Pembelajaran PPKn untuk Meningkatkan Kemampuan Literasi Siswa SD Peterongan - Widiya, Anggita Wahyu; Miyono, Noor; Alexsandri, Luthfi Winarni; Agustini, Ferina (Universitas Nusantara PGRI Kediri, 2024)
Having the ability to read and write is crucial in many aspects of daily life. This study aims to use Wordwall media in the Civics lesson to help fourth graders become more proficient readers and writers. The PTK, or classroom action research technique, is used for the study. Wordwall media in the Civics course serves as the independent variable, while reading proficiency serves as the dependent variable. Observation, testing, and documenting accompanied by quantitative and qualitative analytic approaches were used for data collecting. Twelve kids, thirteen girls and nine boys, from fourth grade at Peterongan Elementary School served as study participants. During the second cycle, the study was conducted. During cycle II, the classical proportion increased to 86% from 73% in cycle I. Wordwall medium may enhance civics-related reading abilities, according to classical percentage statistics.